Perforation of a Meckel’s diverticulum secondary to chronic NSAID use: case report and review of the literature - Espitia, Francisco Terrazas; Davila, David Molina; Ramirez, Luis Villalobos; Trujillo, Bruno Salazar; Moyron, Lucio Santos; Salgado, Ariadna Mondragon (International Surgery Journal, 2020)
Meckel´s diverticulum is an abnormality in the development of the gastrointestinal system, its origin and clinical significance was first described by Johan Friedrich Meckel in 1809. It is a remnant of the omphalomesenteric duct which is usually observed following the rule of 2’s, located 2 feet proximal to the ileocecal valve, before 2 years of age in approximately 2% of the population, and is twice as common in male population. It is considered a true diverticulum because it presents all the histopathological layers of the bowel; 6% of the cases present with heterotopic tissue, mainly pancreatic, gastric, colonic or jejunal. We present the case of a 37-year-old patient who presented with acute onset epigastric pain which migrated to the right iliac fossa, he had a history of chronic non-steroidal anti-inflammatory drugs (NSAIDs) usage for articular pain. He underwent abdominal contrast tomography (CT) scan with double iodine contrast enhancement, which revealed the presence of a perforated Meckel´s diverticulum in the antimesenteric portion of the terminal ileum. The patient underwent laparoscopic diverticulectomy with no complications and was discharged 72 hours after the procedure. Histopathological confirmation of a perforated meckel’s diverticulum with heterotopic gastric mucosa confirmed the clinical suspicion of perforation secondary to chronic NSAIDs usage.